Designing a Web-Based Sales and Ordering Information System with the Zachman Framework: From Business Models to a Technology Roadmap - Nurul Inayah Aulia Anas; Nitha Nurul Fitri Thayyib; Muh. Asyraff A Asmal; Aulya Dialira Zahra; Soussou Raharimalala (Indonesian Journal of Enterprise Architecture, 2025)
The use of the system aims to achieve conformity with business needs, which requires organizations of a certain scale to develop their systems to a level of complexity. Enterprise architecture (EA) is a structured approach used to identify all system requirements and enables the design and development of complex systems to be simpler. In EA modeling, frameworks are used to provide guidance for developers in designing and developing systems. With a framework, developers can easily follow the steps, methods or logical structures provided by the framework. The ease of obtaining information via the internet does not reduce the importance of books as a valid source of information or reference. However, buying books directly often faces several obstacles, such as lack of information about the book you are looking for, difficulty finding books in stores that have many types of books, and offers regarding the stock and place of the book you want. Therefore, an online book sales information system framework based on the Zachman Framework was developed, with the aim of making it easier for book buyers and sellers to transact. The system is designed to have a clean, easy-to-understand, balanced and complete design, and provides features such as book catalogs, company information, payment systems and transaction processing information. The use of the Zachman Framework in designing a website-based book sales and ordering information system provides an effective solution to meet business and user needs.